Emotional Bond Reflected In Donny’s Character In Baby Reindeer Movie - Na’ilah Farashifah; Hariyono; Rindrah Kartiningsih (PT. Padang Tekno Corp, 2026)
This study analyzes the representation of emotional bond in Baby Reindeer movie, focusing on Donny’s emotional attachment to his abuser. Emotional bond refers to a strong psychological connection that develops between individuals through repeated emotional interaction, vulnerability, and dependency. Using a qualitative descriptive method, this research examines selected dialogues and scenes to identify patterns of emotional dependency, empathy toward the abuser, cognitive conflict, and self-blame. The findings show that Donny’s attachment is not rooted in genuine affection, but in fear, vulnerability, and the need for validation. The series portrays emotional bonding as a complex psychological condition that keeps individuals connected to harmful relationships even without physical captivity. This study highlights how contemporary media represents emotional entanglement and the psychological impact of abusive dynamics.